Modulation of Brain Network Topological Properties in Knee Osteoarthritis by Electroacupuncture in Rats - Zhang JP; Shen J; Xiang YT; Xing XX; Kang BX; Zhao C; Wu JJ; Zheng MX; Hua XY; Xiao LB; Xu JG (Journal of Pain Research, 2023)
Jun-Peng Zhang,1,* Jun Shen,2,3,* Yun-Ting Xiang,1,* Xiang-Xin Xing,4 Bing-Xin Kang,5 Chi Zhao,2 Jia-Jia Wu,4 Mou-Xiong Zheng,4,6 Xu-Yun Hua,4,6 Lian-Bo Xiao,2,3 Jian-Guang Xu1,4,7 1School of Rehabilitation Science, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Department of Orthopedic, Guanghua Hospital of Integrative Chinese and Western Medicine, Shanghai, People’s Republic of China; 3Arthritis Institute of Integrated Traditional Chinese and Western Medicine, Shanghai Academy of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 4Department of Rehabilitation Medicine, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 5The First Affiliated Hospital of Henan University of Chinese Medicine, Zhengzhou, People’s Republic of China; 6Department of Traumatology and Orthopedics, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 7Engineering Research Center of Traditional Chinese Medicine Intelligent Rehabilitation, Ministry of Education, Shanghai, China*These authors contributed equally to this workCorrespondence: Jian-Guang Xu, School of Rehabilitation Science, Shanghai University of Traditional Chinese Medicine, 1200 Cailun Road, Shanghai, People’s Republic of China, Email xjg@shutcm.edu.cn Lian-Bo Xiao, Department of Orthopedic, Guanghua Hospital of Integrative Chinese and Western Medicine, 540 Xinhua Road, Changning District, Shanghai, People’s Republic of China, Email xiao_lianbo@163.comIntroduction: Osteoarthritis is a chronic, ongoing disease that affects patients, and pain is considered a key factor affecting patients, but the brain changes during the development of osteoarthritis pain are currently unclear. In this study, we used electroacupuncture (EA) to intervene the rat model of knee osteoarthritis and analyzed the changes in topological properties of brain networks using graph theory.Methods: Sixteen SD rat models of right-knee osteoarthritis with anterior cruciate ligament transection (ACLT) were randomly divided into electroacupuncture intervention group and control group. The electroacupuncture group was intervened on Zusanli (ST36) and Futu (ST32) for 20 min each time, five times a week for 3 weeks, while the control group was applied sham stimulation. Both groups were measured for pain threshold. The small-world properties and node properties of the brain network between the two groups after the intervention were statistically analyzed by graph theory methods.Results: The differences are mainly in the changes in node attributes between the two groups, such as degree centrality, betweenness centrality, and so on in different brain regions (P< 0.05). Both groups showed no small-world characteristics in the brain networks of the two groups. The mechanical thresholds and thermal pain thresholds were significantly higher in the EA group than in the control group (P< 0.05).Conclusion: The study demonstrated that electroacupuncture intervention enhanced the activity of nodes related to pain circuit and relieved pain in osteoarthritis, which provides a complementary basis for explaining the effect of electroacupuncture intervention on pain through graphical analysis of changes in brain network topological properties and helps to develop an imaging model for pain affected by electroacupuncture.Keywords: osteoarthritis, electroacupuncture, pain, spatio-temporal analysis, neural plasticity